Application of response surface methodology for COD and ammonia removal from municipal wastewater treatment plant using acclimatized mixed culture - Ya'acob, Amirah; Zainol, N.; Aziz, Nor Hazwani (Elsevier Ltd, 2022)
This study aimed to optimize conditions influencing the removal of chemical oxygen demand (COD) and ammonia-N in municipal wastewater by using acclimatized mixed culture (AMC). Two-level factorial analysis was used to investigate the factors affecting the degradation of COD and ammonia-N (%); ratio of synthetic wastewater (SW) to acclimatized mixed culture (AMC) (1:1 and 3:1), presence and absence of support media (Yes and No), agitation (0 rpm and 100 rpm) and hydraulic retention time (HRT) (2 and 5 days). A central composite design (CCD) under response surface methodology (RSM) determined the optimum agitation (0 rpm and 100 rpm) and retention time (2 and 5 days). The best conditions were at 3:1 of SW: AMC ratio, 100 rpm agitation, without support media, and 5 days retention time. COD and ammonia-N removal achieved until 57.23% and 43.20%, respectively. Optimization study showed the optimum conditions for COD and ammonia-N removal were obtained at 150 rpm agitation speed and 5 days of retention time, at 70.41% and 64.29% respectively. This study discovers the conditions that affect the COD and ammonia-N removal in the municipal wastewater using acclimatized mixed culture.